2008
DOI: 10.1088/0031-8949/78/03/035402
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of shock waves in a dusty gas with heat conduction, radiation heat flux and exponentially varying density

Abstract: The propagation of shock waves in a dusty gas with heat conduction and radiation heat flux, in which density varies exponentially, is investigated. The dusty gas is assumed to be a mixture of small solid particles and a perfect gas. The equilibrium flow conditions are assumed to be maintained, and the heat conduction is expressed in terms of Fourier's law and the radiation is considered to be of the diffusion type for an optically thick grey gas model. The thermal conductivity K and the absorption coefficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 41 publications
4
34
0
Order By: Relevance
“…Values of initial volume fraction Z o for some values of k p and σ are calculated from the equation (13).Initially taking shock strength U/a o =12 at r=1.1 for k p =0.1, σ=50, b̅ =0.02, Z o =0.00222, β=0.16, =1.4=1, λ=1.1 and Γ=1.36 the variation of shock velocity, shock strength, non-dimensional pressure and non-dimensional flow velocity with propagation distance(r) have been calculated and displayed through figures (1)(2)(3)(4)(5)(6)(7)(8)(11)(12)(13)(14). It is observed that shock strength increases asymptotically as cylindrical shock implodes in the medium.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Values of initial volume fraction Z o for some values of k p and σ are calculated from the equation (13).Initially taking shock strength U/a o =12 at r=1.1 for k p =0.1, σ=50, b̅ =0.02, Z o =0.00222, β=0.16, =1.4=1, λ=1.1 and Γ=1.36 the variation of shock velocity, shock strength, non-dimensional pressure and non-dimensional flow velocity with propagation distance(r) have been calculated and displayed through figures (1)(2)(3)(4)(5)(6)(7)(8)(11)(12)(13)(14). It is observed that shock strength increases asymptotically as cylindrical shock implodes in the medium.…”
Section: Resultsmentioning
confidence: 99%
“…The governing equations for one dimensional, unsteady, adiabatic and cylindrical symmetrical flow of a mixture of real (non-ideal) gas and small spherical solid particles can be written as [12]- [14] u u 1 p u 0 t r r …”
Section: Basic Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [8] and Viashwakarma [9] using similarity method. He found that the presence of small solid particles in the medium has significant effect on the variation of density and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…al. [11]. Yadav et al [12] studied the propagation of weak cylindrical shock in the mixture of ideal gas and dust particle in presence of constant axial magnetic field.…”
mentioning
confidence: 99%